Migration Phenomen and The Interpretation of The Main Influencing Factors, The Case of Albania - Kolleshi, Flavia (European Journal of Multidisciplinary Studies, 2023)
Albania is one of the most suitable grounds for the study of the phenomenon of migration based on its multidimensional forms, referring to international migration, internal migration, return, etc. Likewise, the Albanian state is a country that most clearly reflects the correlation between development as a whole and migration in particular. It is evident that emigration has been a major element for the country’s transition towards a more developed and "modern" economy and society. If we refer to the macro level, immigrants’ remittances have made a substantial contribution to the structure of the country’s gross domestic product since the beginning of the 1990s, a period that also belongs to the first years of democracy in the country. Meanwhile, at the micro level, they have made a very significant contribution to the survival and progress of many Albanian families for a long time. On the other hand, the migration has been to such a degree that it has brought about a disruption of the balance of the country’s population, causing a division between the highly chaotic urbanized edge of the Tirana region and the depopulation of the mountainous and hilly rural areas in north, south and interior of the country. The multiple interactions of several population and migration variables, cause a general concern for Albania’s demographic and economic future. All these changes and phenomena related to migration in all its forms are based on several factors (such as historical, economic, political, social, cultural, etc.), which we will consider in this paper in order that we not only identify but also try to deal with some theories that have been tried to interpret these issues.